Charting a New Direction and Strategy in Nepal’s Foreign Policy - Pandey, Nischal Nath (Journal of Foreign Affairs, 2021)
Despite assorted contributions to the understanding of how Nepal’s foreign policies are formulated, and how different actors and factors shape and implement them, foreign policy research remains largely centered in the Ministry of Foreign Affairs. But it doesn’t mean that the increasing importance of other actors can be ignored. Thus, this paper aims to discuss a dire need to revamp our institutional structures regarding foreign policy decision-making and implementation to suit the new challenges and opportunities that have come on the way because of changes and transformation in the global and national politics. This research identifies the growing number of actors in foreign policy decision-making and implementation along with the changing geopolitical and geo-economic scenario of Nepal, and concurrently reiterates that Nepal must comprehensively overview the efficacy of other ministries and departments that influence foreign policy making and implementation to bring into synergy. Hypothesising that Nepal’s foreign engagement can be robust with policy coordination and structural change, the paper gives a way forward to improve and adapt to the changes, and chart a new direction for Nepal’s foreign relations.